Fruit flies as a powerful model to drive or validate pain genomics efforts. (November 2013) - Leung, Calvin; Wilson, Yana; Khuong, Thang M; Neely, G Gregory
Chronic pain is a disabling condition that persists even after normal healing processes are complete and presents considerable physical, psychological and financial burdens for patients globally. However, current analgesic treatments do not meet clinical needs. Here, we review genomic and pharmacogenomic studies of pain in humans and nociception in the fruit fly Drosophila melanogaster, and provide evidence supporting the use of fly genetics to compliment genome-wide and pharmacogenomic studies of human conditions, such as pain. Combining genomic and pharmacogenomic techniques to study chronic pain in humans with functional genomic assessment in model organisms may provide molecular rationale for developing more personalized or improving generalized chronic pain therapies.